Annual update and practice issues for preparation, compilation, and review engagements - Parker, Hugh; Hunter, Kelly J.; Burke, Kimberly (Newark : John Wiley & Sons, Incorporated, 2017)
Do you need to be compliant with all the professional standards surrounding engagements performed in accordance with Statements on Standards for Accounting and Review Services (SSARSs)' Written by expert authors, one of whom participated heavily in the standard setting, this title is a practice-oriented review of the latest developments related to SSARS Nos. 21, 22, and 23, the last two of which were issued in 2016. A go-to reference for training staff and managing preparation, compilation, and review engagements, this course includes case studies and lively discussion among the experienced participants, making this class informative and practical. This book helps: -Identify the professional standards and risk factors relevant to the planning of preparation, compilation, and review engagements.-Identify responses to preparation, compilation, and review engagement practice issues that comply with all applicable professional standards.
Includes index.
Keywords: ACCOUNTING STANDARDS